The effects of powerholder gender and race /ethnicity on gaining compliance in the classroom - Elias, Steven Michael, author; Loomis, Ross J., advisor (Colorado State University. Libraries, 2001)
A 2 X 2 X 3 between subjects design was used to determine what impact an instructor's gender and race/ethnicity might have on his or her ability to gain compliance in the classroom when utilizing various bases of social power. It was hypothesized that student perceptions of, as well as compliance rates with, social power bases would differ when examining such instructor characteristics. Participants were 297 undergraduate students who completed the Interpersonal Power Inventory while viewing photos depicting male and female faculty members of varying ethnicities (Caucasian Non-Hispanic, African American, and Latino). Student perceptions of faculty members' power usage being either harsh (overt and punitive) or soft (subtle and non-coercive) differed based on instructor gender and race. For example, female instructors using legitimate position power were perceived as using a harsh power type, where as male instructors using the same power type were perceived as using a soft power base. Caucasian Non-Hispanic instructors using legitimate dependence power were perceived as using a soft power type, where as the same power type, when used by a minority instructor, was perceived as being harsh. Female faculty members consistently obtained higher compliance rates when utilizing soft, as opposed to harsh, bases of power. However, male instructors were able to use harsh or soft bases of power without compromising student compliance. With regard to individual power bases, male instructors obtained greater compliance ratings than female instructors when utilizing impersonal reward and informational power. Several findings lend support to the theory of modem racism in that perceptions of, as well as compliance with, power usage favored Caucasian Non-Hispanic faculty members. For example, when utilizing personal reward power, Caucasian Non-Hispanic instructors obtained greater student compliance rates than did Latino instructors. These results indicate that although male and female instructors of varying ethnicities are in the same physical environment when in the classroom, they are in differing social environments. As a result, such an issue should be considered when planning future instructors' courses of training and mentorship. Furthermore, the current study indicates that when utilizing power, what works for one instructor might not work for another.
Keywords: social psychology; teacher education